Analysis of Jerold E. Kemp Learning Model on Students Learning Outcomes at SD Negeri Kuripan 04, Kesugihan, Cilacap - Ima Yuni Pasaningsih; Kuntoro Kuntoro (UM Purwokerto Press, 2025)
This study aims to analyze the effect of the Jerold E. Kemp learning model on student learning outcomes at SD Negeri Kuripan 04, Kesugihan, Cilacap. This study uses a descriptive qualitative approach that aims to describe in depth how the application of the Kemp learning model can affect student learning outcomes at SD Negeri Kuripan 04, Kesugihan, Cilacap. The subjects in this study were teachers and grade V students involved in the learning process. Data were collected through observation, interviews, and documentation. The results showed that the Kemp learning model which focuses on structured and continuous planning can increase student involvement in teaching and learning activities. The application of clear and systematic steps in this model makes it easier for teachers to deliver material, and motivates students to be more active in understanding the subject matter. Based on these findings, it can be concluded that the application of the Jerold E. Kemp learning model has a positive impact on student learning outcomes, by improving student understanding and skills at SD Negeri Kuripan 04, Kesugihan, Cilacap.